Migrasi ke Jakarta: Pendekatan Yustisi atau Pemasaran Kota? Migrating to Jakarta: Legal Operation or City Marketing Approach? - Nurhadi, Moh. (VITASPHERE, 2012)
Inward migration is a common phenomenon in Jakarta especially before and after Lebaran (Moslem Holy Day). In that moment, a lot of people who are mostly marginal groups are coming to Jakarta to seek jobs. These inward migrant are typically workforce with limited education and therefore lays on informal sectors. Due to the characteristic of inward migrants. the city government tends to reject the migrants through legal operations in the train and bus station. The city government believes that accept migrants will only increase their budget operationfor public services, in contrary there will be no contribution of migrant to the city. It looks like that the city is only a market for investor, business, industry, and high quality residents. This article tries to identify the advantage and disadvantage of legal operation approach by comparing it to city marketing approach. Result of this comparison will be used as recommendation for city to deal with inward migration.